Prevention of pacemaker lead induced tricuspid regurgitAtion by transesophageal eCho guidEd implantation (PLACE Pilot). (14th October 2021) - Gmeiner, J; Sadoni, S; Orban, M; Fichtner, S; Estner, H; Massberg, S; Hagl, C; Naebauer, M; Hausleiter, J; Braun, D
Abstract: Background: Lead-induced tricuspid regurgitation (TR) is a frequent complication after pacemaker- and ICD-implantation that is associated with increased mortality and hospitalizations. Purpose: The aim of this pilot study was to investigate if lead implantation guided by transesophageal echocardiography (TEE) is feasible and might be able to reduce lead-associated TR. Methods: 21 patients with indication for new pacemaker/ICD including a trans-tricuspid lead implantation and TR < grade 2+ were prospectively enrolled and underwent TEE-guided lead implantation in addition to fluoroscopy. Leads were placed according to a dedicated echo protocol with focus on a transgastric en face view of the tricuspid valve targeting a lead position in a tricuspid valve commissure (preferentially postero-septal) and an apical ventricular lead position. (Figure 1) Transthoracic echocardiography (TTE) was performed before implantation and at discharge. 121 consecutive patients with standard lead implantation guided by fluoroscopy only served as a historical control group. TR was assessed by an experienced cardiologist and graded according to current guidelines. Results: Key baseline characteristics of overall 124 patients with a mean age of 74 years didn't differ between groups. Of note, there was no significant difference regarding device type and baseline TR. TEE-guided lead implantation was possible in all 21 patients in the TEE-group in deep conscious sedation without occurrence of serious adverse events. Lead placement in a commissure, mostly postero-septal, was possible in 95.2% of patients without worsening of TR (20/21 pts). Based on TEE-guidance, lead position or length was altered in 52.4% of patients (11/21 pts, 6 pts with lead repositioning, 5 pts with modification of lead length). Compared to baseline, the 21 patients in the TEE-group did not show worsening of TR at discharge. In contrast, TR worsening by one grade occurred in 13.6% of patients (14/103 pts) with new onset of TR ≥2+ in 6.8% of patients (07/103 pts) in the control group (p=0.001). At discharge, lead position was evaluated using 2D and 3D TTE in a subset of patients. In all examined patients (14/14 pts) lead position was unchanged compared to intraprocedural position and stable during inspiration vs. expiration as well as in upright vs. horizontal position. Conclusion: TEE-guidance during PM/ICD-implantation was safe and feasible and resulted in steps to optimize lead position in a relevant number of patients. At discharge lead position remained stable and TEE-guided lead implantation was associated with less worsening of TR than standard lead implantation guided by fluoroscopy. Funding Acknowledgement: Type of funding sources: None.